Computational Thinking through Cooperative Games in Elementary - Josko, João Marcelo Borovina; Amaral, Sérgio Ferreira do (Anais do Workshop sobre Educação em Computação (WEI); 2025: Anais do XXXIII Workshop sobre Educação em Computação, 2025)
This study explores an unplugged approach to teaching computational thinking (CT) by integrating cooperative games into physical education. Addressing gaps in interdisciplinarity between CT and Physical Education and replicability, the intervention introduced sequencing and single repetition steps to fourthand fifth-grade students in a Brazilian public school. Led by a trained teacher, the study used semi-structured field notes, teacher remarks, and assessments to evaluate engagement and learning. Results showed that embodied activities fostered collaboration and CT understanding, though challenges like group coordination and distractions affected outcomes. The study presents a replicable model for interdisciplinary CT learning in resource-limited settings.